DIVERSION IN THE PERSPECTIVE OF ISLAMIC LAW - Farhan Fathur Rahman (RADJA PUBLIKA, 2024)
This text discusses the importance of children as the hope of their parents, nation, and state for the future development of the country. It highlights that the behavior and character of children are often influenced by external factors such as social environment, leading to cases where children come into conflict with the law. The text also explores the different definitions of children in positive law, Islamic law, and the Convention on the Rights of the Child. It emphasizes the changes in the legal system for children in conflict with the law, focusing on the shift from treating children as objects to providing special protection and adopting restorative justice and diversion. The text also addresses the role of parents in guiding children and the need for their education to prevent legal violations. The research methodology used is library research and normative legal doctrinal research, focusing on restorative justice and diversion. The findings emphasize the importance of protecting the rights and interests of children in conflict with the law and the potential of restorative justice and diversion in addressing this issue. The text also compares the concepts of diversion in positive law and Islamic law, highlighting differences in the age of legal capacity and the types of criminal acts eligible for diversion. The implications of the study are significant for legal and social systems in providing effective protection and justice for children in conflict with the law.